Treinamento em Análise Funcional Baseada em Tentativas para avaliação comportamental em sala comum - Ferrari, Isadora Peresi (Universidade Federal de São Carlos, 2019)
Trial-based Functional Analysis is an adapted procedure from traditional Functional Analysis methodology to be used among classroom activities. The idea is to investigate problem behavior’s function by experimentally arranging its antecedent and consequent events. Such arrangements verify if problem behavior is maintained by positive reinforcement in form of attention or access to favorite objects, negative reinforcement through escaping from academic demands, or automatic reinforcement by self-stimulation. The present study investigated to what extent literature empirically supports TBFA in regular classrooms through a literature review. It also conducted a second study to verify the effects of a training protocol over a Sign Language Teacher to conduct Trial-based Functional Analysis to assess problem behavior at regular classroom with death children. To do so, a training protocol was implemented in five phases: Initial evaluation, Pre-training + Baseline, Training and Post-training. The Training Program effects were observed by calculating and comparing procedural fidelity while the teacher was conducting the Trial-based FA at Baseline, Role-play, Post-training and Tracking 1, 2 and 3 phases. The Inter Observer Agreement was 80%. The overall results indicate that the Training helped to improve teachers’ repertoire to conduct Trial-based FA even when not all conditions have reached 100% of procedural fidelity. Literature review indicated that ethical and methodological aspects, as well as the lack of data from post evaluation impacts on the natural environment may not contribute to itsfeasibility of implementation. Data from teacher training showed that the teacher was able to conduct TBFA with high integrity and with few time trainings. However, training costs, application in regular classroom and the absence of teacher’s autonomy to conduct the assessment did not support TBFA implementation in regular Classroom. Discussions and future research suggestions are further presented.
Trial-based Functional Analysis training for behavioral assessment at regular classroom
Keywords: Educação Especial; Análise do comportamento; Análise Funcional Baseada em Tentativas; Protocolo de treinamento; Treinamento de professores; Special Education; Behvior analysis; Trial-based Functional Analysis; Training protocol; Teacher training; CIENCIAS HUMANAS